Environmental & architectural phenomenology. Vol. 5, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 1994)
Vol. 5, No. 3, Fall 1994 (includes “items of interest,” "citations received,” book reviews of Christopher Day's Places for the Soul & Yi-Fu Tuan's Passing Strange and Wonderful, and essays by Michael Lincourt & Harvey E. Sherman).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals